Pro Java EE 5 Performance Management and Optimization - Haines, Steven (Apress : Imprint: Apress, 2006)
Pro Java EE 5 Performance Management and Optimization features proven methodology to guarantee top-performing Java EE 5 applications, and explains how to measure performance in your specific environment. The book also details performance integration points throughout the development and deployment lifecycles that are crucial for application success. For quality assurance and preproduction stages, this book guides you through testing and optimally deploying your Java EE 5 applications, with a focus on assessing capacity and discovering saturation points. It defines the concept and application of wait-based tuning-one of the most effective approaches to application server tuning. The book also helps you assess and improve the health of your applications upon deployment. The topics covered include trending, forecasting, and capacity assessing and planning. When production issues arise, you'll be armed with troubleshooting methodology and solutions to common problems that have been observed in real-world environments. This book even guides you through the creation of a formal Java EE 5 performance management plan customized to your environment to help you interpret and react to changing trends in usage patterns.